Risk factors for acute diarrhoea in children between 0 and 23 months of age in a peri-urban district of Pakistan: a matched case–control study. Issue 3 (14th May 2022) - Sadiq, Kamran; Mir, Fatima; Jiwani, Uswa; Chanar, Suhail; Nathwani, Apsara; Jawwad, Muhammad; Hussain, Amjad; Rizvi, Arjumand; Muhammad, Shah; Habib, Muhammad Atif; Soofi, Sajid Bashir; Ariff, Shabina; et al.
Abstract: Background: Diarrhoea is a leading cause of preventable childhood morbidity and mortality worldwide. Unfortunately, Pakistan has the third-highest burden of diarrhoea-related deaths in children <5 y of age. Therefore we aimed to evaluate factors associated with diarrhoea among Pakistani children. Methods: A retrospective 1:2 matched case–control study nested in a baseline cross-sectional survey was conducted from October to December 2018 in Taluka Kotri, a two-thirds urban locality in the Jamshoro district. Children between the ages of 0 and 23 months with a history of diarrhoea in the 2 weeks preceding the survey were labelled as cases. Age-matched controls were children without symptoms of diarrhoea. Univariate and multivariable conditional logistic regression was performed to identify diarrhoea-related factors. Results: A total of 1558 cases were matched with 3116 controls. Factors significantly associated with lower odds of diarrhoea in the multivariate analysis included increasing maternal age (odds ratio [OR] 0.78 [95% confidence interval CI 0.67 to 0.90]), breastfeeding (OR 0.77 [95% CI 0.66 to 0.90]), higher paternal education (OR 0.79 [95% CI 0.65 to 0.97]) and belonging to the rich (OR 0.66 [95% CI 0.54 to 0.80]) and richest quintiles (OR 0.54 [95% CI 0.44 to 0.66]). Conclusions: This study identifies risk factors associated with diarrhoea in children <23 months of age, including younger maternal age, higher paternal education, not breastfeeding and poverty, which has implications for developing preventive programs and strategies that target populations with a higher risk of diarrhoea.